Removed material volume calculations in CNC milling by exploiting CAD functionality - Benardos, Panorios; Vosniakos, George-Christopher (Inderscience, 2017)
Material removal volume calculations in machining processes are important in a variety of milling simulation applications, including material removal rate estimation and machining force calculation. In this paper two different approaches are presented to this end, i.e., Z-maps and Boolean operations with solid models. The Z-map method is simple but results in large files and needs sophisticated routines to render acceptable accuracy. Boolean operations between accurate solid models of the tool and the workpiece is implemented on readily available CAD system application programming interface. Beside the computational load which is bound to the accuracy level, it requires a sufficient number of interpolated points through one revolution of the tool to be trustworthy. It is practical to use at particular points of interest along the toolpath.